2020
DOI: 10.1308/rcsann.2019.0147
|View full text |Cite
|
Sign up to set email alerts
|

Tumour length as an independent prognostic factor in resectable oesophageal carcinoma

Abstract: Introduction Oesophageal longitudinal tumour length has been investigated as a prognostic indicator for disease recurrence and overall survival in resectable oesophageal carcinoma. However, there is conflicting evidence regarding its use in clinical practice. This study aims to assess the prognostic significance of histological tumour length in potentially curative oesophageal resections for cancer. Materials and methods Patients with locally advanced oesophageal carcinoma (squamous or adenocarcinoma) were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…In this study, to clarify the impact of the length of the esophageal lesions on the survival rate of patients, we applied the ROC curve analysis method to define the specific cut-off values of the patients in this group. The results show that when the patient's lesion length is ≤4.5 cm, the patient survival rate, and local control rate are better than those patients with esophageal lesion length > 4.5 cm, which is similar to the results reported in the past [8] [9] [10] [11] [12].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, to clarify the impact of the length of the esophageal lesions on the survival rate of patients, we applied the ROC curve analysis method to define the specific cut-off values of the patients in this group. The results show that when the patient's lesion length is ≤4.5 cm, the patient survival rate, and local control rate are better than those patients with esophageal lesion length > 4.5 cm, which is similar to the results reported in the past [8] [9] [10] [11] [12].…”
Section: Discussionsupporting
confidence: 86%
“…The length of esophageal lesion and postoperative pathological staging are important factors affecting the prognosis of patients with EC after surgery (17). Most research results show that the lesion length of EC is closely related to the postoperative pathological stage T and N, and that patients with shorter lesions have relatively early T and N staging (18,19). According to the calculation formula of LODDS, it is clear that LODDS is related to the number of lymph nodes, with smaller LODDS correlating to the earlier stages of a patient's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the present study demonstrated that tumor length was an important prognostic factor for the EC-SM of patients who underwent IMRT. Furthermore, although most studies supported that tumor length is an important prognostic factor for EC, no consensus was achieved on the tumor size cut-off value, which ranges from 2 to 5 cm (31)(32)(33). The results from the present study demonstrated that elevated 2-year EC-SM was observed in patients with tumor length ≥4.5 cm (45.8% vs. <4.5 cm group: 21.4%; P<0.001).…”
Section: Discussionmentioning
confidence: 99%